Clinical, familial, and neuroimaging features of CADASIL‐like patients. (11th August 2014) - Nannucci, S.; Pescini, F.; Bertaccini, B.; Bianchi, S.; Ciolli, L.; Valenti, R.; Dotti, M. T.; Federico, A.; Inzitari, D.; Pantoni, L.
Abstract : Objectives: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited small vessel disease caused by NOTCH3 mutations. There are no clinical and neuroimaging findings pathognomonic of the disease. The aim of this paper was to provide a description of a group of NOTCH3 ‐negative patients with a phenotype closely resembling that of CADASIL. Materials and methods: We performed NOTCH3 analysis (exons 2‐23) in 117 probands because of a clinician's suspicion of CADASIL. The CADASIL scale, a recently developed tool that allows to better select patients for NOTCH3 analysis, was retrospectively applied to NOTCH3 ‐negative patients; the patient subgroup that scored higher than the screening cutoff for CADASIL was defined as CADASIL‐like. Results: Thirty‐four CADASIL‐like patients (mean age at onset 57.8 years [52.1–63.4], 50% males) were identified. Compared with 25 patients with CADASIL for clinical, familial, and neuroimaging features, only the following variables were significantly ( α level <0.05) different in frequency between patients with CADASIL and CADASIL‐like patients: a positive family history for stroke at age ≤60 years, more frequent in patients with CADASIL, and hypertension, more frequent in CADASIL‐like patients. Conclusions: Our experience highlights the growing number of patients presenting with a high suspicion of a cerebral small vessel disease with an autosomal dominant pattern of inheritance and a phenotype closely similar to that of CADASIL but without NOTCH3 mutations. This group remains to be characterized from the genetic point of view. The role of other genes or NOTCH3 alterations on exons other than 2‐23 or introns has to be further assessed.